Self-Switching Kerr Oscillations of Counterpropagating Light in Microresonators - Woodley, Michael T.M.; Hill, Lewis; Del Bino, Leonardo; Oppo, Gian Luca; Del'Haye, Pascal (Physical Review Letters, 2021)
We report the experimental and numerical observation of oscillatory antiphase switching between counterpropagating light beams in Kerr ring microresonators, where dominance between the intensities of the two beams is periodically or chaotically exchanged. Self-switching occurs in balanced regimes of operation and is well captured by a simple coupled dynamical system featuring only the self- and cross-phase Kerr nonlinearities. Switching phenomena are due to temporal instabilities of symmetry-broken states combined with attractor merging, which restores the broken symmetry on average. Self-switching of counterpropagating light is robust for realizing controllable, all-optical generation of waveforms, signal encoding, and chaotic cryptography.
CRIS-Team Scopus Importer:2021-02-12